Cognitive and regulatory characteristics and mathematical performance in high school students. (February 2016) - Morosanova, Varvara I.; Fomina, Tatiana G.; Kovas, Yulia; Bogdanova, Olga Y.
Abstract: The study examined the links of cognitive and regulatory characteristics with mathematical outcomes in high school students. Participants were 318 14–16 year old students from 7 state schools in Russia. A computerised test battery was used to measure aspects of number sense, spatial ability, spatial memory and processing speed. The battery also included two measures of mathematical performance. Academic grades and final school test scores in mathematics were also collected. In addition, the students completed the Self-Regulation Profile of Learning Activity Questionnaire — SRPLAQ, which measures different aspects of self-regulation related to achieving learning goals, such as goal planning, results evaluation, and responsibility. The results suggest that cognitive and regulatory features are independently associated with mathematical performance, and that the links differ depending on the specific aspect of mathematical performance used. Highlights: We investigated links between cognitive and regulatory characteristics of learners and their mathematical performance. Cognitive and regulatory features were independently associated with mathematical performance. Different patterns of associations were observed for different mathematical outcomes. Different processes and contexts underlying different aspects of mathematical performance are discussed.